The International fellowship of reconciliation and the anti-Marcos movements - Aguirre, Arjan P. (Philippine Sociological Review, 2010)
This paper aims to make sense of the relationship between the transnational nonstate actor, International Fellowship of Reconciliation (IFOR) and the Philippine revolution of 1986 (EDSA 1986). Through an investigation of the events that took place prior to the revolution, it claims that IFOR helped shape the outcome of EDSA 1986 through its assistance in the mobilization of the nonviolent anti-Marcos movement in the years prior to the February 1986 revolution. First, at the structural level, following the death of Ninoy Aquino, the favorable conditions both in the domestic and international political opportunity structures allowed the anti-Marcos movements to work hand in hand with the IFOR operatives. Second, at the agentic level, the series of fora, seminars, and workshops on active nonviolence organized by IFOR from 1984 to the weeks leading to the revolution had facilitated the diffusion of the principle and methods of active nonviolence to the anti-Marcos movements. Through frame alignment, the mobilization of anti-Marcos movements became possible during the critical moments of the revolution. This mobilization facilitated the further opening of the domestic political opportunity structures (opening of the political access in the Marcos regime after the snap elections, realignment of the anti-Marcos elites, participation of influential allies, low level of political repression, and opening of the media access) during the days leading to EDSA 1986.